THE IMPORTANCE OF MENTORING AND METHODOLOGICAL SUPPORT SYSTEMS IN IMPROVING PROFESSIONAL ADAPTATION OF SCHOOL PSYCHOLOGISTS (International Conference on Education, Psychology and Humanities, 2026)
Mentoring and methodological support are central mechanisms for improving the professional adaptation of school psychologists. The literature indicates that early-career school psychologists benefit from structured supervision, mentoring, clear evaluation expectations, and access to professional support that helps them manage time, boundaries, case complexity, and professional identity. This article analyzes why mentoring and methodological support are important, how they contribute to adaptation, and what institutional conditions make them effective.
Keywords: school psychologists, professional adaptation, mentoring, methodological support, supervision, early career, professional development, school psychology.